If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) = 18 + -2x Reorder the terms: 4(-3 + x) = 18 + -2x (-3 * 4 + x * 4) = 18 + -2x (-12 + 4x) = 18 + -2x Solving -12 + 4x = 18 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12 + 4x + 2x = 18 + -2x + 2x Combine like terms: 4x + 2x = 6x -12 + 6x = 18 + -2x + 2x Combine like terms: -2x + 2x = 0 -12 + 6x = 18 + 0 -12 + 6x = 18 Add '12' to each side of the equation. -12 + 12 + 6x = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 18 + 12 6x = 18 + 12 Combine like terms: 18 + 12 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 6x+3y=11 | | 9(-12+4z)=-72 | | 5n-200=120n-430 | | 15+1*1=26 | | (n-10)*10=60 | | -18x^2+61x+7=0 | | y/4=-92 | | 2(3x-4)+2=12 | | 9x+18=18x+4 | | 8y=25.6 | | d+6+2x=-3 | | -4x-3+9x+5=-6-8x+20+10x | | 8=8p+13-13p | | 4x-50=62 | | ((x-118.75)/118,75)*100-4=0 | | 8y=2.56 | | 27=6+c | | 5x-7+3x=2x+5 | | 7.68=3w | | 15+11=26 | | X/3-6=14 | | 6/3+3/7 | | P-2=-1/2 | | (2g^2+3x)dx+2+gdy=0 | | 4x+20=4(x-5) | | 3.2=u | | 4v=5.12 | | (9x+5)(2x^2-5x-3)=0 | | 3(-2-4x)=2(2+b) | | 2x-3+6x-8=4+2x | | -3y+7x=15 | | (2g^2+3x)dx+2xgdy=0 |